SISTEM INFORMASI TINDAK LANJUT DATA CALON MAHASISWAPADA DIVISI MARKETING - Yus Jayusman; Rahmat Jaenal; Wafa Fitriani (LPPM STMIK Bandung, 2021)
The term follow up when it is called in indonesia means a follow up. Student is a term for someone who is currently pursuing or undergoing higher education in a college such as a high school, academy, and the most commin is a university. Marketing can be called as the spearhead of a company. So that companies that have good marketing will certainly experience significant development within a certain time. Follow up is needed to produce maximum data processing. Based on these problems, STMIK Bandung has a desire to make good use of information technology through the development of a follow-up system. Because the current follow-up data categorization system is not optimal for data management and reporting when needed. The software development model used is a waterfall and the data flow used is an activity diagram, the programming language is DBMS